Research Group in Orchids, Ecology and Plant Systematics: an inter-institutional initiative for plant conservation and sustainable use in south-west Colombia - Flanagan, Nicola S.; Mosquera Espinosa, A. T.; González, R. T.; Molineros Hurtado, F. H.; Ospina Calderón, N. H.; Cuartas Domínguez, M.; Silverstone Sopkin, P. A.; Reina, G.; Diez, M. C.; Ospina Torres, R.; Ackerman, James D.; Bayman, P.; et al. (Lankesteriana: International Journal on Orchidology, 2013)
.